Perineural invasion as a neuro−immune niche in head and neck cancer: mechanisms of immune evasion and therapeutic implications - Li, Simin; Xiao, Hui (Frontiers in Immunology, 2025)
Perineural invasion (PNI) is a distinct route of spread in head and neck cancer and portends recurrence despite optimized surgery–radiotherapy backbones. Emerging cancer−neuroscience and immuno−oncology insights reframe PNI as a neuro−immune niche, in which neurotrophic signaling (GDNF–RET, NGF–TrkA), Schwann−cell plasticity, and neuromodulators (adenosine via CD39/CD73–A2A; nociceptor−derived CGRP) calibrate tumor behavior and immune tone along cranial nerves. Evidence spanning clinical and experimental models shows matrix−dominated, immune−excluded interfaces; adjuvant radiotherapy and nerve−pathway−directed target design mitigate local risk, while agents (A2A antagonists, TrkA inhibitors, CCR5 blockade) may counter perineural programs. Notably, deployment as immunity enablers remains uncertain, with unresolved issues in PNI quantification, biomarker selection, pharmacodynamic monitoring, and combinations with checkpoint or cellular therapy. In this review, building on cancer−neuroscience frameworks, we synthesize mechanistic drivers of the perineural niche, appraise efficacy− and safety−oriented pathology/imaging readouts and drugging opportunities spanning neural and immunometabolic circuits, and outline sequencing with locoregional measures to restore durable immunity. In addition, we discuss how nociceptor signaling and adenosinergic signaling intersect with Schwann−cell programs to regulate the balance between perineural immunosuppression and anti−tumor immunity. The purpose of this article is to define PNI as a neuro−immune niche in head and neck cancer and delineate biomarker−guided therapeutic strategies for clinical testing.